Association of Spousal Separation and Widowhood with Incident Dementia: The Atherosclerosis Risk in Communities (ARIC) Neurocognitive Study (NCS). (20th December 2022) - Xie, Jiaxin; Pike, James R.; Walker, Keenan A; Sullivan, Kevin J; Windham, B Gwen; Gottesman, Rebecca F
Abstract: Background: Community‐based investigations suggest that being unmarried in mid‐ to late‐life increases dementia risk. However, these studies rarely distinguish the cause of unmarried status (i.e., whether divorced, widowed, or never married). We prospectively examined spousal separation/loss and dementia incidence in the ARIC study. Method: 14, 922 participants reported marital status and were dementia‐free at baseline (Visit 3, 1993‐95; mean age 59.6, SD 5.8). They were followed through 2019 with annual follow‐up surveys of marital status (never married [n = 390], married [n = 7, 314], divorced/separated [n = 1, 512], widowed [n = 5, 706]). Widowed or divorced/separated participants were asked when this event occurred. Dementia cases were adjudicated through in‐person evaluations, informant interviews, and phone assessments from Visit 5 onward, and pre‐ and post‐Visit 5 hospitalization codes and death certificates. We investigated the association between being widowed and being divorced/separated (both as time‐varying variables) with dementia (excluding dementia in the first year after widowhood event) using Cox proportional hazards models, adjusted for demographics, APOEε4, and vascular risk factors. Results: 2, 931 dementia cases were identified. Demographic‐ and APOEε4‐adjusted hazard ratio (HR) (95% CI) for dementia was 1.11 (1.02‐1.21) in participants who were widowed compared to those who were not widowed, when time‐varying widowhood status was considered. (Table 1 ). This association was no longer significant when the model was further adjusted for time‐variant covariates (e.g., vascular risk factors, occupation, health insurance status). A similar pattern was seen for number of times widowed, where results were suggestive of elevated dementia risk in minimally adjusted but not more fully adjusted models. Compared to participants who were neither widowed nor separated, participants who were widowed had a higher unadjusted HR (95% CI) for dementia, HR = 1.78 (1.65‐1.93) vs HR = 0.94 for those who were separated or divorced (0.81‐1.09) (Table 2 ). Conclusion: Widowhood is associated with dementia incidence in minimally adjusted models, with limited evidence that the association is stronger than that which is seen from divorce/separation alone. However, this association was not statistically significant in the adjusted model, indicating that other factors may contribute to the observed relationship.